The 16S and COI Mitochondrial DNA Nucleotide Composition of Stripped Snakehead (Channa striata Bloch,1793) from Lake Sentani, Jayapura, Papua - Christine Bawaeda Sitandung Kombong; Tuty Arisuryanti (Universitas Gadjah Mada, 2018)
Stripped snakehead (Channa striata Bloch,1793) has potency to be developed in Indonesia due to high nutritional value including omega 3 which is useful for children growth. However, study on composition of mitochondrial DNA nucleotide as a part of study on genetic characterization of stripped snakehead fish in Indonesia is poorlyunderstood. Genetic characterization of stripped snakehead is important to obtain data information that can be applied for breeding and conservation program. Therefore, the objective of this study was to determine the 16S and COI mitochondrial DNA nucleotide of stripped snakehead collected from Lake Sentani, Jayapura, Papua. Method used in this research is PCR method using primer 16Sar and 16Sbr for 16S mitochondrial gene, and FishF2 and FishR2 for COI mitochondrial gene. The results showed that composition of 16S mtDNA nucleotide from 616 bp was T=21.92%, C=25.49%, A=30.19%, dan G=22.40%, whereas composition of A+T=52.11% and G+C=47.89%. In addition, composition of COI mtDNA nucleotide from 705 bp was T=29.93%, C=28.65%, A=24.26%, and G=17.16% while composition of A+T=54.48% and G+C=45.52%. Data of 16S and COI mitochondrial DNA nucleotide composition of the stripped snakehead collected from Lake Sentani gained in this study are to be expected to complete genetic information of the fish species which is useful to improve breeding program of this fish species in the future.